Northwest History. Alaska, Glaciers. United States. (1937)
Alaska Glacier On Move Again. FAIRBANKS, Alaska, May 18. (/P)—Black Rapids glacier, continuing its freakish movement, neared the Big Delta river today and stirred apprehension lest it dam the stream, as it was supposed to have done 100 years ago. Across the river from the towering glacier front lay Black Rapids roadhouse, where Colonel H. E. Revell, the proprietor, and his wife and son watched for any sudden movement of the ice which would necessitate their flight. Revell telephoned Fairbanks he dared not venture on the frozen water-laden surface of the river to measure accurately the distance the glacier was from the Big Delta. He said the glacier seemingly had turned upstream. When Black Rapids first started its hurried journey over its old morain last October, observers predicted its forward movement would stop when warm weather came and melted the face faster than it advanced. In February the glacier was a mile and a half from the Big Delta. Its movement varied from a few feet to several yards a day.